MICROTOPONYMY OF BELARUSIAN–LITHUANIAN–POLISH BORDERLANDS - Komara, Veronika (Via Latgalica, 2014)
In the present report we will focus on the analysis of microtoponyms of Bobrovniki (Babrowniki) village and its surroundings. The village is in Ostrovets (Astravets) district (Republic of Belarus, Grodno (Hrodna) region), north-western part of which borders on the Republic of Lithuania. This area is dominated by flat terrain, which, of course, influenced the system of names of geographical objects.Microtoponyms are divided into 2 groups:1) names of onomastic origin, which amounted to 53 % of the total number of microtoponymic units;2) names of apellative origin, which amounted to 47 % of the total number of microtoponymic units collected by us.In the first group of names we have distinguished the units, formed from the stems of official personal proper names, their spoken varieties and place names. Microtoponyms motivated by personal names are especially well represented.In the second group of names we have found the names, formed from common nouns. The study of the structural organization of the names of small geographical objects of the village Bobrovniki and its environment showed, that names simple in their structure are more common than composite ones.Origin of microtoponyms is characterized by heterogeneity. Of course, most of the names come from the ancestral Belarusian stems and roots – lexemes used in the Belarusian language from the times of Proto-Slavic, East Slavic period, id-est Belarusian own words. But there are detected microtoponymic units, formed by borrowed names as well. Among these microtoponyms the names of the Polish and Lithuanian descent have been recorded.Microtoponymic units in the structure of which the suffixes that are typical of the Lithuanian language have been found:-uny- (-un-), rising to the Lithuanian -ūnai;- ishki- dating back to the Lithuanian -iški, -iškė, -iškis, -iška;-oyti (from Lithuanian -aičiai and -aitis).In the study of this area there were also recorded microtoponymic units in the structure of which an element of Lithuanian stems has been detected.Our material collected 24 % of the total number of names of units, that were formed under the influence of Polish and Lithuanian languages. Thus, it is safe to continue to study MICROTOPONYMY of Ostrovets area, and in particular Bobrovniki village and its surroundings. In this area, common names of small geographical objects that appeared in the Belarusian dialects under the influence of neighbouring languages are wide spread.